Early retirement and company characteristics - Erik Hernæs; Fedor Iskhakov; Steinar Strøm (University of Oslo, Department of Economics, 2006)
Early retirement decisions derived from a structural model with economic incentives and firm workforce changes, are estimated on Norwegian linked household and firm data. For households in which the wife is the first to become eligible for early retirement, the impact on early retirement of a reduction in the firm workforce is stronger relative to economic incentives than is the case for men, in particular in the private sector. Both for men and women, also an expansion of the firm workforce implies a higher retirement probability.The eligibility age in the early retirement programme has gradually been reduced from 66 in 1989 to 62 in 1998. We find that the economic incentives relative to the push factor have become more important, both for men and women, the lower the eligibility age is.
Keywords: C35; J26; 330; Early retirement; demand side and supply side factors; microeconometric models; heterogeneity; Flexible Altersgrenze; Männer; Frauen; Arbeitsangebot; Arbeitsnachfrage; Norwegen; Ökonometrisches Modell